Transcriptome Profiling Analysis Reveals the Potential Mechanisms of Three Bioactive Ingredients of Fufang E’jiao Jiang During Chemotherapy-Induced Myelosuppression in Mice - Li, Xue; Zhang, Yan; Hong, Zhuping; Gong, Shuqing; Liu, Wei; Zhou, Xiangshan; Sun, Yangen; Qian, Jing; Qu, Haibin (Frontiers in Pharmacology, 2018)
Although multiple bioactive components have been identified in Fufang E'jiao Jiang (FEJ), their hematopoietic effects and molecular mode of action in vivo are still not fully understood. In the current study, we analyzed the effects of martynoside, R-notoginsenoside R2 (R2), and 20S-ginsenoside Rg2 (Rg2) in a 5-fluoracil (5FU)-induced myelosuppression mouse model. Bone marrow nucleated cells (BMNCs) counts, hematopoietic progenitor cell colony forming unit (CFU) assay, as well as flow cytometry analysis of Lin-/c-kit+/Sca-1+ hematopoietic stem cell (HSC) population were conducted, and bone marrow (BM) cells were subjected to RNA sequencing. The transcriptome data were processed based on the differentially expressed genes (DEG). The results of the analysis show that each of the three compounds stimulates BMNCs and HSC growth, as well as burst-forming unit-erythroid (BFU-E) and colony-forming unit granulocyte-monocyte (CFU-GM) colony expansion. The most relevant transcriptional changes appeared to be involved in regulation of hematopoietic cell lineage, NF-κB and TNF-α signaling, inhibition of inflammation, and acceleration of hematopoietic cell recovery. Notably, the individual compounds shared similar but specified transcriptome profiles. Taken together, the hematopoietic effects for the three tested compounds of FEJ are confirmed in this myelosuppression mouse model. The transcriptome maps of these effects provide valuable information concerning their underlying mechanisms and provide a framework for the continued study of the complex mode of action of FEJ.